Atlas Reuse. Tools for the architectural reuse in Barcelona - Mària Serrano, Magda; Santolaria Castellanos, Ana Isabel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The Atlas of architectural reuse deals with the study of buildings that have changed use over time in Barcelona, ​​including activities for which they had not been designed, as well as possible architectural strategies to program these changes of use successfully in the future. This article explains the functioning of the Atlas Reuse, the methodology used, and the multiple readings on the city that it allows. It also presents new lessons derived from this research up until now. In this way, the Atlas reveals its potential as a versatile and valuable tool that offers a diagnosis of reuse in Barcelona in the present, but at the same time, allows us to extract useful strategies for planning the city of the future.